Rekonstuksi Paradigma Manajemen dan Kurikulum Transformatif Dalam Implementasi Filsafat Pendidikan Islam Inklusif Kontemporen - Deden (IAI Al Muhammad Cepu, 2025)
This study explores the reconstruction of transformative management and curriculum paradigms in the implementation of inclusive Islamic education philosophy in a contemporary context. The research problem arises from the stagnation of conventional Islamic education practices that are still normative and less adaptive to social change. This study aims to develop a conceptual and practical curriculum and management model that integrates philosophical values, inclusive principles, and transformative educational goals. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews, and document analysis in three Islamic educational institutions that have implemented inclusive curriculum innovations. The research findings reveal that transformative management and curriculum reconstruction in Islamic education emerged through three key processes: philosophical reorientation based on monotheism and justice; managerial reform emphasizing participatory leadership; and pedagogical transformation integrating religious knowledge and modern science. These processes foster a more inclusive, humanistic, and reflective learning environment. This study concludes that reconstructing the Islamic education paradigm requires a holistic synergy between curriculum design, institutional management, and philosophical foundations. The resulting Transformative Curriculum Management Model Based on the Philosophy of Inclusive Islamic Education offers theoretical and practical contributions to strengthening the relevance and adaptability of Islamic education in an era of global transformation.